2018
DOI: 10.1016/j.contraception.2017.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to accessing abortion services and perspectives on using mifepristone and misoprostol at home in Great Britain

Abstract: The presence of multiple barriers to accessing abortion care in Great Britain highlights the need for future guidelines to recommend a more woman-centered approach to service provision. Reducing the number of clinic visits and designing services to meet the needs of those living in controlling circumstances are particularly important goals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 23 publications
1
66
0
4
Order By: Relevance
“…However, those living in states with middle‐ground and supportive laws also experienced access barriers, including long distances to clinics, lack of transportation and difficulty finding information. These issues echo women's reasons for seeking medication abortion online in countries with few legislative barriers to clinical care, such as Great Britain . Also, we found that self‐managed medication abortion can be a preference for some women, regardless of state legislative context.…”
Section: Discussionmentioning
confidence: 57%
“…However, those living in states with middle‐ground and supportive laws also experienced access barriers, including long distances to clinics, lack of transportation and difficulty finding information. These issues echo women's reasons for seeking medication abortion online in countries with few legislative barriers to clinical care, such as Great Britain . Also, we found that self‐managed medication abortion can be a preference for some women, regardless of state legislative context.…”
Section: Discussionmentioning
confidence: 57%
“…Question 1 asked women to rank potential barriers to abortion care from a list of five commonly cited barriers 5. Women were asked to rank the options as 1, 2 or 3, where a ranking of ‘1’ was indicative of the most difficult barrier.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, there have been refinements in service delivery for medical abortion in the first 9 weeks of pregnancy, with more self-management of the process, including home administration of misoprostol3 and simplified follow-up methods such as self-assessment of the procedure’s success using low-sensitivity urine pregnancy tests at home 4. Nevertheless, a qualitative study from 2018 indicated that as many as 519 women who reside in Britain had contacted the non-profit organisation 'Women on Web ' over a 4-month period to try to access medical abortion drugs via the internet 5. The reasons given for trying to access abortion in this way highlighted personal and logistical barriers faced by women through the British healthcare system.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently it has been interpreted in UK law that both drugs should be administered on licensed premises. This obligation to return to the abortion service (often a hospital or remote clinic) for a second visit impacts many women who struggle with repeated time off work, childcare, transport difficulties or distance from the abortion service 16. Furthermore, it selectively disadvantages the most vulnerable – those who are deprived, live in rural areas or have dependents.…”
Section: Home Use Of Abortifacientsmentioning
confidence: 99%